How useful are molecular assays in breast cancer in the elderly?. (June 2013) - Bundred, Nigel J
Breast cancer in the elderly represents a major public health issue, which is expected to increase in the coming decades as the population ages. Despite evidence suggesting that standard adjuvant therapy confers clinical benefit and is well tolerated overall in elderly patients, currently, in clinical practice, elderly breast cancer patients are undertreated. This perspective discusses contemporary clinical practices and challenges in the treatment of elderly breast cancer patients and highlights the roles of molecular assays, including Onco type DX ®, MammaPrint ®, Mammostrat ® and IHC4, in optimizing patient care in this population. The perspective also discusses the potential future role of functional molecular assays (e.g., the assessment of Ki-67 levels after short-term aromatase inhibitor therapy) in predicting therapy benefit.